Euthanasia of freedom and sexual conatus - Kordela, Aglaia Kiarina (Filozofski vestnik, 2025)
One of the tours de force in Joan Copjec’s Read My Desire concerns the correlation be-tween the Lacanian formulas of sexuation and the Kantian antinomies of reason. This paper traces the modern itinerary of freedom, from the dynamic antinomy (male side) and Kant’s free public world Scholar of the Enlightenment, through Marx’s democratic State as the locus of transcendent freedom, to Copjec’s sex qua real, i.e., as a freedom that emerges out of the signifier’s own non-symbolizable effects. Accordingly, today’s gender and other identitarian self-proclamations—whose “dico, ergo sum”: “I say, there-fore I am” (Jacques-Alain Miller) endeavors to subsume one’s being under the signifier and, hence, eliminate the real—amount to the euthanasia of freedom. Opposing this de-velopment, this essay proposes Spinoza’s substance qua power of self-actualization and immanent causality, as well as the singular conatus (striving to persevere in one’s one being), as key ontological concepts required to sustain the two intertwined aspects of the real as both (an impossible) pre-symbolic cause and (an increasingly prohibited, yet in-evitable) post-symbolic effect.
Keywords: glasba; Lacan, Jacques; music; psihoanaliza; psychoanalysis; Spinoza, Baruch de